The sage handbook of mixed methods research design - Poth, Cheryl N. (55 City Road : Sage Publications Ltd, 2023)
The Sage Handbook of Mixed Methods Research Design is a ground-breaking edited work that weaves together diverse perspectives and global examples of mixed-methods research to present a timely picture of this rapidly evolving field. With contributions from over 80 of the biggest names and rising stars of the field, this Handbook is an essential resource for anyone interested in the contemporary, emerging, and evolving practice of mixed methods research and scholarship. Exploring new and novel applications of existing mixed methods research design practices, the handbook provides comprehensive integration guidance while showcasing how design innovations inspire and contribute to investigating previously under-researched social issues and populations. Through its unique focus on design and the diverse contexts in which mixed methods research is being applied, this Handbook prepares researchers for the changing conditions in which they will conduct studies. Newcomers and seasoned mixed methods researchers alike will find this Handbook a go-to source for tools to think and act 'complexively' and creatively in research design. Using accessible language and illustrative examples, this Handbook is written for those with various roles and experience in mixed methods research design. The in-depth discussions led by the interdisciplinary group of 11 internationally renowned editorial section leads project our collective thinking of mixed methods research design into the future across the following six sections: Section 1: Inspiring Diversity and Innovation in Mixed Methods Design; Section 2: The Craft of Mixed Methods Research Design; Section 3: Expanding Mixed Methods Design Approaches; Section 4: Designing Innovative Integrations with Technology; Section 5: Navigating Research Cultures in Mixed Methods Design; and Section 6: Exploring Design Possibilities and Challenges for Mixed Methods Research.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mixed methods research